Implementation of Perilaku Hidup Bersih dan Sehat (PHBS) from an early age - Rani Maharani; Najla Nadhifa; Adam Syahbani (Universitas Pendidikan Indonesia, 2024)
Perilaku Hidup Bersih dan Sehat (PHBS), or Clean and Healthy Living Behavior, is a form of individual response to the environment to minimize the emergence of various diseases caused by behavior from everyday life. To increase this awareness, it needs to be done early so that it becomes a good habit for the community. This community service was carried out by students of the Indonesian Education University with the theme